Food-derived protein hydrolysates and peptides: anxiolytic and antidepressant activities, characteristics, and mechanisms - Wenhui Li; Yu Xi; Junru Wang; Yinxiao Zhang; He Li; Xinqi Liu (Food Science and Human Wellness)
Globally, the prevalence of anxiety and depression has reached epidemic proportions. Food-derived protein hydrolysates and peptides delivered through dietary supplementation can avoid the negative risks associated with traditional pharmaceuticals while delivering superior anxiolytic and antidepressant effects. This review summarizes current research on food-derived anxiolytic and antidepressant protein hydrolysates and peptides, and subsequently analyses their physicochemical characteristics and elaborates on their mechanisms. The aim of this work is to contribute to the in-depth study and provide a theoretical foundation for the development of related products to better serve patients with anxiety and depression.